The lion king [videorecording (DVD)] - John, Elton; Zimmer, Hans (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
"Embark on an extraordinary coming-of-age adventure as Simba, a lion cub who cannot wait to be king, searches for his destiny in the great 'Circle of Life'"--Container.